Growth hormone responses to acute resistance exercise with vascular restriction in young and old men - Manini, Todd M. (2012)
OBJECTIVE: Resistance exercise (RE) stimulates growth hormone (GH) secretion in a load-dependent manner, with heavier loads producing larger GH responses. However, new research demonstrates that low-load RE performed with blood flow restriction (BFR) produces potent GH responses that are similar to or exceed those produced following high-load RE. We hypothesized that low-load RE with vascular restriction would attenuate the known age-related reduction in GH response to RE. DESIGN: In a randomized crossover design, ten young (28±7.8 years) and ten older (67.4±4.6 years) men performed bilateral knee extension RE with low-load [20% of one-repetition maximum (1RM)] with BFR and high-load (80% 1RM) without BFR. GH and lactate were measured every 10 minutes throughout a 150-minute testing session (30 minutes prior to and 120 minutes following completion of the exercise); IGF-I was measured at baseline and 60 minutes post-exercise. RESULTS: Area under the GH curve indicated that both age groups responded similarly to each exercise condition. However, young men had a significantly greater maximal GH response to low-load RE with BFR than the high-load condition without BFR. Additionally, younger men had greater maximal GH concentrations to low-load RE with BFR than older men (p=0.02). The GH responses were marginally correlated to lactate concentration (r=0.13, p=0.002) and IGF-I levels were unchanged with RE. CONCLUSIONS: GH responses to low-load RE with vascular restriction are slightly higher than high-load RE without vascular restriction in young men. However, low-load RE with vascular restriction did not attenuate the known age-related reduction in GH response with exercise. These data suggest that while low-load RE with vascular restriction is as effective for inducing a GH response than traditionally-based high-load RE, there is a more potent response in young men.